3-(5-(Benzylideneamino)thiazol-3-yl)-2H-chromen-2-ones: a new class of alkaline phosphatase and ecto-5′-nucleotidase inhibitors. Issue 25 (22nd February 2016) - Saeed, Aamer; Ejaz, Syeda Abida; Shehzad, Muddasar; Hassan, Sidra; al-Rashida, Mariya; Lecka, Joanna; Sévigny, Jean; Iqbal, Jamshed
Abstract : Most plausible binding mode of7h against h -TNAP. Abstract : A new series of 3-(2-(benzylideneamino)thiazol-4-yl)-2 H -chromen-2-ones has been synthesized. The structures of the compounds were established by means of 1 H and 13 C NMR spectroscopy. All compounds were evaluated for their potential to inhibit human recombinant ecto-nucleotidases, including human tissue-nonspecific alkaline phosphatase ( h -TNAP), tissue specific human intestinal alkaline phosphatase ( h -IAP), human and rat ecto-5′-nucleotidase ( h -e5′NT & r -e5′NT). All the compounds were found to be potent and selective inhibitors of h -e5′NT, the most active h -e5′NT inhibitors were compounds7a (IC50 = 0.25 ± 0.07 μM) and7g (IC50 = 0.28 ± 0.05 μM). Most of the compounds were found to selectively inhibit h -TNAP over h -IAP, with inhibitory activities in the lower micromolar range. The most active h -TNAP inhibition was exhibited by compounds7h and7c (IC50 = 0.21 ± 0.04 μM and 0.22 ± 0.03, respectively), which is ≈91 times greater than the inhibitory activity of the standard inhibitor levamisole. Compound7i was found to be the most potent h -IAP inhibitor (IC50 = 0.05 ± 0.001 μM), exhibiting ≈11 times greater selectivity for h -IAP over h -TNAP. Homology modeling, molecular docking and dynamics studies were carried out to determine the most plausible binding site interactions of potent inhibitors with ecto-nucleotidases.